Protopanaxadiol and Protopanaxatriol-Type Saponins Ameliorate Glucose and Lipid Metabolism in Type 2 Diabetes Mellitus in High-Fat Diet/Streptozocin-Induced Mice - Jianjun Deng; Jianjun Deng; Yao Liu; Yao Liu; Zhiguang Duan; Zhiguang Duan; Chenhui Zhu; Chenhui Zhu; Junfeng Hui; Junfeng Hui; Yu Mi; Yu Mi; et al. (Frontiers in Pharmacology, 2017)
Ginsenoside is a major active component of ginseng, which exhibits various pharmacological properties such as hepatoprotection, tumor suppression and diabetes resistance. In this study, the anti-diabetic effects of protopanaxadiol (PPD) and protopanaxatriol (PPT)-type saponins were explored and compared in high-fat diet/streptozocin-induced type 2 diabetes mellitus (T2DM) mice. Our results showed that low or high dose (50 mg/kg bodyweight or 150 mg/kg bodyweight) PPD and PPT significantly reduced fasting blood glucose, improved glucose tolerance and insulin resistance in T2DM mice. PPD and PPT also regulated serum lipid-related markers such as reduced total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol in T2DM mice. In addition, PPD and PPT dramatically ameliorated the inflammatory responses by suppressing the secretion of pro-inflammatory cytokines like tumor necrosis factor-alpha and interleukin-6 in serum level and gene expression in liver level, and improved the antioxidant capacity by increasing the superoxide dismutase and decreasing malondialdehyde levels in the serum of T2DM mice. Moreover, the anti-diabetic effect of PPD and PPT appeared to be partially mediated by the suppression of hepatic metabolism genes expression such as peroxisome proliferator-activated receptor gamma coactivator 1-alpha, phosphoenolpyruvate carboxykinase, and glucose-6-phosphatase, as well as facilitating lipid metabolism genes expression such as microsomal TG transfer protein in the liver tissues of T2DM mice. Taken together, our results indicated that PPD and PPT might potentially act as natural anti-diabetic compounds to be used for preventing and treating the T2DM and its complications in the future.